Aquifer system and depth specific chemical patterns in fractured-rock groundwater from the Critical Zone revealed by untargeted LC-MS-based metabolomics. (1st July 2022) - Sanchez-Arcos, Carlos; Ueberschaar, Nico; Pohnert, Georg
Highlights: Groundwater metabolomics reveals below ground biogeochemical processes. Mass spectrometry identifies patterns of DOM fluxes and transformations in the aquifer. Input of DOM by above-ground processes, transformation and transport can be distinguished. Marker-free work allows identification of microbial contributions to DOM structure. Land-use type, aquifer system, and sampling depth determine metabolome patterns. Abstract: In the Earth's Critical Zone, water plays an essential role as a collector and transporter of metabolites and their transformation products. It is generally believed that the chemical profiles of groundwater are strongly impacted by land use. However, predictors for the effects of above-ground natural and anthropogenic activities on below-ground chemistry are rare. We reasoned that comparing groundwater metabolomes from different land-use sites and depths can give insight into this coupling of above and below-ground processes in the Critical Zone. This study used an LC-MS-based untargeted metabolomic approach to identify links between groundwater metabolomes from monitoring wells in fractured carbonate-/siliciclastic alternations along a hillslope of the Hainich Critical Zone Exploratory (CZE) in Thuringia, Germany. Our results identify the land-use type, aquifer system, and sampling depth as critical factors determining the differences among groundwater metabolomes. We established five groundwater metabolic clusters and correlated these to the aquifer systems, hydrogeochemistry, and microbial community composition. Our untargeted metabolomic approach reveals the limited connectivity of groundwater chemical profiles with above-ground activities and illustrates how deep the input signals can travel. Graphical abstract: Image, graphical abstract